Increased circulating cytokine levels in African American women with obesity and elevated HbA1c. (April 2020) - Williams, Ariel; Greene, Natasha; Kimbro, K.
Highlights: Obese African American women express unique population of cytokines. IL-3, IL-4, IL-7, TNF-α, IFN-α2, & CX3CL1 are differential expressed due to HbA1c. Several cytokines in this study are correlated with BMI, HbA1c & lipids. Several cytokines in this study are correlated with BUN/Creatinine & electrolytes. Abstract: Purpose: Obesity has emerged as one of the biggest health crisis and is the leading cause of death and disabilities around the world. BMI trends suggest that majority of the increase in T2D is resulting from the increased prevalence of obesity. In fact, 85.2% of people with T2D are overweight or obese. The highest prevalence for obesity is seen in non-Hispanic, African American women (56.6%). T2D is classified as an inflammatory disease because of elevated, circulating pro-inflammatory cytokines and acute-phase inflammatory proteins. This study was designed to determine how high HbA1c and serum glucose correlate with circulatory cytokine levels in obese, African American women. Methods: We investigated cytokine/chemokine serum levels using a multiplex assay. Then we used Pairwise Pearson Correlation Test to determine the relationship between clinical metabolic parameters and cytokine/chemokine serum levels. Results: The results indicated that participants with elevated HbA1c exhibited an up regulation of IL-3, IL-4, IL-7, TNF-α, IFN-α2 and CX3CL1 serum levels compared to participants with normal HbA1c. These cytokines were also correlated with several clinical metabolic parameters. Conclusions: The results suggest that IL-3, IL-4, IL-7, TNF-α, IFN-α2 and CX3CL1 serum levels may contribute to the development and onset of type 2 diabetes.